Parameter for Process Validation of Sevelamer Hydrochloride Film Coated Tablet - Thakur, Aditya; Joshi, Deshbandhu; Singh Bhadauria, Raghvendra (International Journal of Scientific Research and Management (IJSRM), 2022)
Validation is a tool of quality assurance which provides confirmation of the quality in equipment system, manufacturing process, software and testing methods. Validation of the individual step of manufacturing processes is called the process validation. The concept of validation was first proposed by two Food and Drug Administration(FDA) officials, Ted Byers and Bud Loftus, in the mid-1970s in order to improve the quality of pharmaceuticals Assurance of product quality is derived from careful attention to number of factors including selection of quality parts and materials, adequate product and process design, control of the process, and in process and end product testing. Process Validation has now become a part of Current Good Manufacturing Practices Regulations (cGMP), it is mandatory for manufacturer to go through Process Validation much more rigorously than earlier. Coating process proven as validated from the weight build up data of tablets as validation data provided for after 50%coating, 75% coating and 100% coating and found in accordance with process validation protocol. Finished product result was evidence of Weight gain while the inspection activity as this material is in very high hygroscopic in nature. However results found within specified limit